Common fixed point theorems for compatible mappings - Kenan Taş; Mustafa Telci; Brian Fisher (International Journal of Mathematics and Mathematical Sciences)
By using a compatibility condition due to Jungck we establish some common fixed point theorems for four mappings on complete and compact metric spaces These results also generalize a theorem of Sharma and Sahu.